Ofsted and Special Measures: A Student Perspective - Dubas, Rachael (2013)
The aim of this investigation was to explore the student perspective of Ofsted Inspection and Special Measures within a Northern England Secondary School. It is widely acknowledged that the staff perspective of Ofsted and Special Measures is varied but very little research has been conducted into the perspective of the student. As Ofsted are clear that the needs of the child are a significant priority to them, and that Student Voice in itself is becoming more widely recognised and respected, this investigation had clear justification. In order to explore these perspectives, four Research Questions were composed. Firstly, what do students understand the purpose of Ofsted to be? Secondly, how did students perceive the initial and subsequent Ofsted Inspections? Thirdly, what do students understand the grade "Special Measures" to mean? Lastly, what is the student perception of the changes taking place as a result of the "Special Measures" grading?